Multicriterial Analysis on Selecting Solar Radiation Concentration Ration for Photovoltaic Panels Using Electre-boldur Method. (2016) - Naghiu, George Sebastian; Giurca, Ioan; Aşchilean, Ioan; Badea, Gheorghe
Abstract: The selection of the optimal solution regarding the concentration ratio is a complex process, as it depends on a very high number of criteria. The production of renewable energy using the concentrated solar radiation is a field of high scientific level worldwide, while in Romania the research in this field is only in its early stages. The purpose of this document is to present a classification method for photovoltaic systems taking into account the concentration ration. The paper tries to fill in a gap in the field of choosing the photovoltaic systems from the concentration ratio perspective. Based on the study performed, we recommend using the variant A4, namely the technical solution consisting of a photovoltaic system with a 1000x concentration ratio.